Effect of nitrogen fertilization and shade type in soil quality and nitrogen assimilation in Ecuadorian Amazon Coffea canephora agroecosystems - Ibarra L., Rosa E. (Zamorano: Escuela Agrícola Panamericana, 2020., 2020)
In the Amazon basin, Robusta (Coffea canephora) is produced in contrasting agroecosystems of low input, shade-based smallholder production, or in intensively managed monoculture plantations that differ in nitrogen (N) availability and productivity. This study aimed to determine whether the shade trees and proper addition of N-fertilizer in coffee plantations may provide soil fertility benefits and contribute to soil quality and crop productivity. Full sun had a positive effect on enzyme activities, potentially mineralizable N (PMN), available ammonium (NH4-N), leaf %N and leaf N:P. Enzyme activities as well as NH4-N were greater under low input, whereas high input yielded greater PMN, leaf N and leaf N:P. Protease was positively associated with PMN (R = 0.60, P = 0.003) but unrelated to the activities of the aminopeptidases, and carbon (C) mineralizing enzymes. Permanganate oxidizable C (POXC) and nitrate (NO3-N) were similar across input and shade managements but more variable under shade relative to full sun. Low input offers limited improvements in soil N cycling increasing by 53% the enzymatic activity and N availability by 31% relative to high input under Robusta coffee production in this region. Whereas, high input improves PMN and Robusta N uptake (Leaf N). Relatively lower response in enzymatic activities, C and N stocks, and leaf N under shade management suggests that although it is a common smallholder practice in this region, leguminous tree-based agroforestry may not close N needs of Robusta as effectively as higher N inputs.